Photoresponse properties based on CdS nanoparticles deposited on multi-walled carbon nanotubes. Issue 81 (16th August 2016) - Hu, Chenglong; Wang, Yuan; Chen, Shaoyun; Cheng, Huan; Lin, Mei; Zhang, Yuanfang; He, Dan; Liu, Xueqing; Liu, Jiyan
Abstract : The deposition of CdS on MWCNT has been successfully achieved by an attaching noncovalent chemical approach. The PCE of CdS@MWCNT nanohybrids was found to be as high as 4.54%, contrasting sharply with the value (1.67%) of the pure CdS nanoparticles. Abstract : The influence of multi-walled carbon nanotube ( i.e. MWCNT) architectures for facilitating charge transport in CdS semiconductor films was investigated. The power conversion efficiency (PCE) of the CdS nanoparticle-deposited multi-walled carbon nanotube nanohybrids ( i.e. CdS@MWCNT) could be enhanced when the MWCNT was employed as the conducting scaffold in the CdS nanoparticle based photoelectrochemical cell. The CdS nanoparticles were deposited onto the MWCNT surface to improve photoinduced charge separation and transport of carriers (electrons and holes). The PCE of the CdS@MWCNT nanohybrids solar cell was found to be as high as 4.54%, contrasting sharply with the value (1.67%) for pure CdS nanoparticles. The outcome of the present work might provide a new avenue for designing optoelectronic and light-energy conversion devices.